ARE JOINT POSITION SENSE, TWO-POINT DISCRIMINATION, FINE MOTOR CONTROL, GRIP STRENGTH, LIGHT TOUCH SENSATION, PAIN, AND FUNCTIONALITY AFFECTED BILATERALLY IN UNILATERAL CARPAL TUNNEL SYNDROME? - Gülfem Ezgi Özaltın; Havva Adlı; Burcu Talu (İstanbul Tıp Fakültesi Dergisi)
Objective: This study aimed to evaluate joint position sense, two-point discrimination, fine motor control, grip strength, light touch sensation, pain, and functionality in patients with unilateral carpal tunnel syndrome and to determine whether these variables change in the unaffected hands of patients with unilateral carpal tunnel syndrome. Materials and Methods: The study was planned as a single-blind, cross-sectional case-control study. Individuals between the ages of 20-65 who were diagnosed with carpal tunnel syndrome (n=22) and healthy (n=22) were included. The device was designed for the study of measurements; discriminator; 9-hole peg test, dynamometer, and pinch meter, Semmens Weinstein monofilament test; The visual analog scale was evaluated bilaterally with the Boston questionnaire. Results: There was a significant difference between all measurements in the affected and unaffected hands between the CTS group and the control group (p<0.05). There was no significant difference between the joint position sense, two-point discrimination, fine motor control, grip strength, light touch sense, and functionality between the affected and unaffected hand in the CTS group (p>0.05). Conclusion: This is the first study evaluating joint position sense in the wrist, metacarpophalangeal joints, and interphalangeal joints in unilateral CTS syndrome. It was noteworthy that patientswith unilateral carpal tunnel syndrome had deficiencies in joint position sense, fine motor control, two-point discrimination, light touch sense, and grip strength compared to the healthy control group, as well as deficiencies in the unaffected sides.